Europejskie przywództwo. Niemcy w Unii Europejskiej - Młynarski, Andrzej (Rocznik Integracji Europejskiej, 2015)
This paper is an attempt to analyse European leadership and the role played by a reunited Germany in the European Union. The author proposes five fundamental theses: 1) the reunification of Germany ruined the balance of power in Europe; 2) the Eastern enlargement of NATO and the EU has moved the zone of political and military influence of the USA to the line of the Bug river; 3) the Germans have confirmed their position as a European power; 4) the foreign policy of Angela Merkel is a continuation of Gerhard Schroder’s policy, meaning a transfer of the focus from European policy to prioritising German national interests; 5) the German issue has remained open.